Hypertension in Hypoxia - Sheetal, Chawla; Rashi, Singhal; Prasenjit, Guchhait (Journal of Hypertension and Cardiology, 2014)
An overview of blood pressure regulation in hypoxia addresses altitude physiology, sleep disordered breathing, and cardiopulmonary disease. It reviews pathophysiology and therapeutic implications.